IS NASOGASTRIC DECOMPRESSION NECESSARY IN ELECTIVE ENTERIC ANASTOMOSIS? - Shamil, Nadia; Quraishi, Shamim; Riaz, Samreena; Channa, Asghar; Maher, Mumtaz (Journal of Ayub Medical College Abbottabad, 2010)
Background: Placement of nasogastric tube is common surgical practice after bowel anastomosis. What is to be achieved by this prophylaxis is gastric decompression, a decreased likelihood of nausea and vomiting, decreased distension, less chance of pulmonary aspiration and pneumonia, less risk of wound separation and infection, less chance of fascial dehiscence and hernia, earlier return of bowel function and earlier discharge from hospital. We conducted a prospective observational study in Surgical Ward 2, Jinnah Postgraduate Medical Centre, Karachi from January 2008 to December 2009 to assess whether routine use of nasogastric decompression in elective enteric anastomosis can be safely omitted. Method: Patients who underwent elective enteric anastomosis were included in this study. These patients were managed prospectively without nasogastric decompression. Outcome were measured in terms of time of passing flatus, nausea, vomiting, abdominal distension, pulmonary complications, wound infection, wound dehiscence, anastomotic leak, length of hospital stay and mortality. Results: Except for incidence of minor symptoms like nausea or vomiting, omission of NG tube did not lead to any serious complication like anastomotic leak, pulmonary complications wound dehiscence or death. Conclusion: Nasogastric decompression can safely be omitted from a routine part of postoperative care after elective enteric anastomosis. Keywords: Nasogastric, Decompression, Elective, Enteric, Anastomosis